GAMBARAN MOTIVASI LANSIA DALAM PEMANFAATAN PELAYANAN KESEHATAN DI POSYANDU LANSIA PUSKESMAS RANTANG MEDAN KOTA TAHUN 2013 - eka jaya; Linda T Maas; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Motivation is a passion in one individual that going to move to act. Motivation can he also defined as a process may indicate an attitude to achieve a target aiming to fulfill his/her need either resourced from one self individual (intrinsic factor) or from out one self individual (extrinsic factor). For one has a motivation indicated he/she get a desire to achieve succeed and may got success also in life This study aimed to identify the description in motivation of those eldest in having health service at Posyandu Lansia Puskesmas Rantang Kota Medan Clinic for 2013. This study adopted a descriptive method with cross sectional approach, in having sample with purposive sampling technique, involved 56 respondents. The location of research is at Posyandu Ixinsia Puskesmas Rantang Medan eldest clinic. The data used in this research such as primary data that has been taken directly from respondent. In research, indicated that a motivation of those eldest mostly categorized in sufficient note (44.6%). For intrinsic factor, noted the requirements of the eldest in having service of Posyandu clinic because the eldest required medical in health treatment about (98.2%), hoping visiting Posyandu Clinic for healing from weakness (92.9%), the eldest have passion to visit Posyandu because they have aware for the importance of Posyandu for the eldest (85.7%). For the extrinsic factor, noted the family encourage the eldest to visit and there got guidance in many exercises (92.9%), the distance of living get near around make them may visit the Posyandu clinic noted (71.4%). The eldest got health services no charge every time to visit the clinic noted (89 3%). It is concluded that motivation of the eldest should he encouraged more run into a good category. To push every the eldest to come in one willingness every time provide a Posyandu clinic program special for the eldest, at least the official of Puskesmas should improve their promotion to invite those eldest to visit more and frequently Posyandu clinic.